Efficacy of a mouthwash containing essential oils and curcumin as an adjunct to nonsurgical periodontal therapy among rheumatoid arthritis patients with chronic periodontitis: A randomized controlled trial - Divvi Anusha; Preetha Elizabeth Chaly; Mohammed Junaid; J E Nijesh; K Shivashankar; Shyam Sivasamy (Wolters Kluwer Medknow Publications, 2019)
Purpose: The purpose of this study was to assess the efficacy of mouthwash containing essential oils and curcumin (MEC) as an adjunct to nonsurgical periodontal therapy on the disease activity of rheumatoid arthritis (RA) among RA patients with chronic periodontitis (CP). Materials and Methods: A triple-blinded controlled trial was conducted among 45 female RA patients with CP randomized into three treatment groups as follows: Group A: scaling and root planing (SRP) with 0.2% chlorhexidine mouthwash as an adjunct (n = 15), Group B: SRP with MEC as an adjunct (n = 15), and Group C: SRP alone (n = 15). RA disease activity was assessed using erythrocyte sedimentation rate, serum C-reactive protein, serum anti-citrullinated protein antibody, and serum rheumatoid factor. Periodontal disease activity was assessed using plaque index, clinical attachment level (CAL), and pocket depth (PD). All parameters were recorded at baseline and 6 weeks thereafter. Data were assessed using one-way ANOVA and paired t-test. Results: A significant reduction in periodontal and RA disease activity parameters was observed from baseline to 6 weeks following intervention (P < 0.05). The highest percentage of mean reduction in plaque index and RA parameters from baseline to 6 weeks was observed in Group B followed by Groups A and C. The highest percentage of mean reduction in PD and CAL was observed in Group A followed by Groups B and C (P < 0.001). Conclusion: This study reveals that MEC as an adjunct to SRP is effective in reducing the disease activity of RA and CP, thereby warranting the use of the same.